2022
DOI: 10.3390/ma15217605
|View full text |Cite
|
Sign up to set email alerts
|

Influence Mechanism of Ageing Parameters of Cu-Cr-Zr Alloy on Its Structure and Properties

Abstract: The Cu-1.0% Cr-0.1% Zr alloy in a solid solution state was investigated by ageing treatments at different temperatures and holding times. The structure and performance were characterized and tested by using X-ray diffraction (XRD), a transmission electron microscope (TEM), a universal material testing machine, and an eddy conductivity detector. The influence laws of ageing temperature and the holding time on the structures and properties of the Cu-Cr-Zr alloy were analyzed. Results demonstrated that, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…As shown in Figure 9b, the Cr precipitates show circular and oval shapes, which is consistent with the discovery by Chbihi et al [34]. Ma et al [35] concluded that there were concentration gradients among different sizes of Cr precipitates in the Cu matrix. The diffusion of Cr atoms promotes the formation of large-sized Cr phases and the dissolution of small-sized Cr phases.…”
Section: Phase Compositionsupporting
confidence: 90%
“…As shown in Figure 9b, the Cr precipitates show circular and oval shapes, which is consistent with the discovery by Chbihi et al [34]. Ma et al [35] concluded that there were concentration gradients among different sizes of Cr precipitates in the Cu matrix. The diffusion of Cr atoms promotes the formation of large-sized Cr phases and the dissolution of small-sized Cr phases.…”
Section: Phase Compositionsupporting
confidence: 90%
“…The mechanical properties of the CuÀ CrÀ Zr alloy are improved by the aging process. This is because high density chromium nano-precipitated phases are produced after aging [11,12]. The addition of chromium and zirconium to copper alloys improves the wear resistance, strength and heat resistance of the alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between chromium and zirconium element atoms is good. Therefore, refining the chromium precipitated phases can further increase the copper alloy's strength [11]. Chromium plays an important role in the mechanical and tribological properties of not only copper alloys but also different alloys [13][14][15].…”
Section: Introductionmentioning
confidence: 99%